1985
DOI: 10.1136/jcp.38.9.1030
|View full text |Cite
|
Sign up to set email alerts
|

Small vessel disease in progressive diabetic neuropathy associated with good metabolic control.

Abstract: SUMMARY Clinical, electrophysiological, and electron microscopical data are presented on 10 diabetic patients with severe progressive neuropathy, predominantly motor in type, in the presence of good blood glucose control, and for one patient with painful neuropathy and third cranial nerve palsy. Endothelial cell hyperplasia was seen in small vessels in all cases, and seven patients showed plugging of the vascular lumen by degenerate cellular material and electron dense protein. It is suggested that these cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 5 publications
4
34
0
1
Order By: Relevance
“…Peripheral neuropathy is the most prevalent neurological sequelae, present in ϳ60% of individuals with non-insulin-dependent diabetes (2). Although the precise mechanisms underlying human diabetic neuropathy remain controversial, a consensus of research indicates that microvascular ischemia is a final common pathological event (3,4). Despite the established importance of microangiopathy, no prior studies have investigated the role of impaired native thrombomodulin (TM)-protein C antithrombotic mechanisms in the pathogenesis of diabetic neuropathy.…”
mentioning
confidence: 99%
“…Peripheral neuropathy is the most prevalent neurological sequelae, present in ϳ60% of individuals with non-insulin-dependent diabetes (2). Although the precise mechanisms underlying human diabetic neuropathy remain controversial, a consensus of research indicates that microvascular ischemia is a final common pathological event (3,4). Despite the established importance of microangiopathy, no prior studies have investigated the role of impaired native thrombomodulin (TM)-protein C antithrombotic mechanisms in the pathogenesis of diabetic neuropathy.…”
mentioning
confidence: 99%
“…In man, nerve biopsy studies have shown that when there is significant diabetic neuropathy, severe microvascular abnormalities [4][5][6][7][8][9][10] are present. In addition, the degree of vessel disease correlates with the severity of nerve damage [6,10] and the multifocal pattern of nerve fibre loss suggests ischaemia [8,9].…”
mentioning
confidence: 99%
“…It can be assumed that, depending on the severity and duration of diabetes, it is the degree of spinal reorganization, due to the degeneration of small afferents, for example, which leads to the deafferentation of spinal neurons and the abnormal branching of A-b fibers. [16,45,47] Moreover, the anatomical framework of the spinal cord allows the transfer of specific inputs to localized subsets of dorsal horn neurons. This allows the separation in signal transduction pathways for low-intensity stimuli and noxious stimuli.…”
Section: Methodsmentioning
confidence: 99%
“…[15] The best predictor of T2DM macrovascular complications is the preceding presence of microvascular complications, particularly diabetic polyneuropathy (DPN) and diabetic nephropathy (DN). [2] DPN consists of demyelization and axonal degeneration of peripheral nerves, [16], leading to slowing of nerve conduction velocity and reduction of the amplitude of the compound muscle and sensory nerve action potentials. [16,23] These features of diabetic polyneuropathy are observed in human diabetes [16,24] and in experimentally induced diabetic animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation